Health Education on Pregnant Women's Gymnastics at the Murni Midwife Clinic, North Padang Lawas Regency - Harahap, Ica Fauziah; Bella, Cindya; Habidah, Habidah; Helmalia, Helmalia; Pohan, Melia Sintia Mutiara (PT Inovasi Pratama Internasional, 2024)
This community service is themed